Explaining Change: The Online Political Marketing of the Romanian Social Democrats. (17th October 2020) - Grad, Marius; Marian, Claudiu
Abstract : In the most recent two decades, the political campaigns conducted by the Social Democratic Party in Romania targeted specific groups of voters, with little intention to attract new voters. The reason behind their strategy is that they could secure a relatively constant support of roughly one third of the electorate and so win the popular vote in every election since 2000. However, the 2016 parliamentary elections marked a turning point in this approach and the party used almost exclusively online marketing to organize, streamline and channel its messages. This article seeks to understand why this change occurred although it did not seem to be necessary. This change is more surprising in a context in which the main political competitors were weak and disorganized. Our qualitative analysis aims to identify and explain the main elements that determined this change. It accounts for three main variables: experiential learning, the role of a new party leader and the use of new opportunities.